How to Use Negotiation Jiu Jitsu to Resolve Conflicts and Persuade. - Negotiation Institute, American; Christian, Kwame (linkedin.com, 2021)
In this course, adapted from the Negotiate Anything podcast, Doug Witten shows you how to use jiu jitsu as a powerful persuasive technique in three easy steps.